Combustion synthesis and excellent photocatalytic degradation properties of W18O491. Issue 31 (21st August 2015) - Chen, Pengqi; Qin, Mingli; Zhang, Dezhi; Chen, Zheng; Jia, Baorui; Wan, Qi; Wu, Haoyang; Qu, Xuanhui
<x xml:space="preserve">Abstract</x> One-dimensional W18O49 nanoneedles were fabricated by solution combustion synthesis and exhibited an excellent visible light-driven photocatalytic performance.